Finite Element Modelling and On-Site Measurements for Roof Mounted Photovoltaic Solar Panels under High Wind Load - Mehranfar, Shayan (Université d'Ottawa / University of Ottawa, 2014)
The application of dynamic wind load on photovoltaic (PV) solar systems mounted on flat roofs influenced their structural behavior significantly. It is implied that when the PV solar system is exposed to extreme weather characteristics such as low temperatures, these might influence the load distribution along each layer of the solar panel, which is composed by multiple layers of different materials. Therefore, the high record of weather characteristics as one scenario in addition to the field experiment were designed to describe parametric structural behavior of PV solar system help to increase the precision of study. According to the mentioned procedures different parameters of weather characteristics measured with instrumentation at the site of PV panel installation at the University of Ottawa where the low temperature equal to -24.3° C and wind speed of 11.8 recorded. The mechanical and thermal properties of full-scale specimen and load application that computed based on weather record for every two minutes of January and February from northern side of specimen, introduced to FEM software SAP 2000. Moreover, the support structure and connection used to assemble real specimen considered in modeling with respect to average temperature equal to -7° C that caused to simulate 36 different cases to compare with simultaneous experiment designed to measured strain within same period. The second investigation involved instrumenting a full-scale PV solar panel specimen with 13 half-bridge strain gauges on both surfaces of the PV solar panel, which were used to measure strain values in longitudinal and transversal directions of solar panel and also on the top and bottom edges of the same panel. According to an equivalent uniform Young’s modulus numerically determined for the five layers of the PV solar panel, and with respect to the Hook’s law, the stresses were found to be equal to 50 Mpa for strain gauges at the mid area of PV solar panel,. This value was used to calibrate boundary conditions of the FE model namely the Fix-Equal and the Pin-Equal conditions along the edges of the solar panel and along the mounting frame.
Keywords: Finite Element Modelling; On-Site Measurements; Photovoltaic Solar Panels; High Wind Load; Parametric Study; Stress Distribution